2016
DOI: 10.1038/srep27413
|View full text |Cite
|
Sign up to set email alerts
|

Programmable DNA Nanosystem for Molecular Interrogation

Abstract: We describe a self-assembling DNA-based nanosystem for interrogating molecular interactions. The nanosystem contains a rigid supporting dumbbell-shaped frame, a cylindrical central core, and a mobile ring that is coaxial with the core. Motion of the ring is influenced by several control elements whose force-generating capability is based on the transition of single-stranded DNA to double-stranded DNA. These forces can be directed to act in opposition to adhesive forces between the ring and the frame thereby pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…A growing repository of DNA nanostructures are now available that show dynamic actuation and reconfigurability in response to external stimuli; this is also what helps distinguish the potential of this class of technology from most other sensor types. [14a,46,116] Reconfigurability enables designing distinct positive and negative states (target present or absent) in DNA‐based sensors thereby reducing signal noise commonly found in existing sensing techniques. For instance, electrochemical biosensors, wherein analyte detection is transduced into an electrical signal, when integrated with DNA structures showed enhanced signal to noise and, in some cases, amplified the signal since the probe was physically much closer to the sensing electrode .…”
Section: Dna Nanostructures As Biomedical Sensorsmentioning
confidence: 99%
“…A growing repository of DNA nanostructures are now available that show dynamic actuation and reconfigurability in response to external stimuli; this is also what helps distinguish the potential of this class of technology from most other sensor types. [14a,46,116] Reconfigurability enables designing distinct positive and negative states (target present or absent) in DNA‐based sensors thereby reducing signal noise commonly found in existing sensing techniques. For instance, electrochemical biosensors, wherein analyte detection is transduced into an electrical signal, when integrated with DNA structures showed enhanced signal to noise and, in some cases, amplified the signal since the probe was physically much closer to the sensing electrode .…”
Section: Dna Nanostructures As Biomedical Sensorsmentioning
confidence: 99%
“…The results showed that the DNA origami devices could detect up to 100 nM of protein with a response time of about 20 min. Strand displacement by the target [88] coupled to the force present in base-stacked DNA duplexes [89] is the most common way to activate the opening of a DNA origami complex. However, these techniques are limited to the nM concentration range and the response times are in the range of minutes or longer.…”
Section: Fluorescence (Förster) Resonance Energy Transfer (Fret)-based Sensorsmentioning
confidence: 99%
“…For instance, a self-assembled DNA-based nanosystem combining a dumbbell-shaped frame, a cylindrical core and a mobile ring was employed for molecular interrogation being able to evaluate base stacking adhesion and detection of a soluble nucleic acid viral genome mimic. The motion of the nanosystem ring can be induced by a transition between single-stranded DNA to double-stranded DNA which show different rigidity, enabling its use as a mechanism for molecular detection at the ring-frame interface [390].…”
Section: Nanomachinesmentioning
confidence: 99%